2022
DOI: 10.2174/1871527320666211008150347
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol Elicits Prolongevity by Increasing Resistance to Oxidative Stress in C. elegans

Abstract: Aim: To analyze the efficacy of eugenol on longevity by assessing its antioxidant effect using Caenorhabditis elegans as an animal model. Background: Eugenol is a major polyphenolic component of Ocimum sanctum (Tulsi) which attributes wide pharmacological activities and can serve as a biomarker. However, the possible effect of eugenol on longevity in Caenorhabditis elegans has not been reported. Objective: The objective of this investigation was to provide first scientific based results about effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Parween et al showed that eugenol significantly improved healthy ageing and slowed neurodegeneration in a CL4176 worm (Caenorhabditis elegans) Alzheimer’s model by enhancing oxidative stress resistance and slowing paralysis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parween et al showed that eugenol significantly improved healthy ageing and slowed neurodegeneration in a CL4176 worm (Caenorhabditis elegans) Alzheimer’s model by enhancing oxidative stress resistance and slowing paralysis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eugenol has been reported in in vitro and in vivo models, enabling a range of pharmacological applications. Among these, it can be mentioned: anti‐inflammatory, 29 analgesic, 30 anaesthetic, 31,32 antioxidant 9,10 and neuroprotective activities 6,7,11 . The antioxidant potential of Eugenol is based on hydroxyl radicals scavenging, and by reduced glutathione (GSH), reducing the formation of reactive oxygen species (ROS) 7,27,33,34 .…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Some foods or other items used in gastronomy were also evaluated. These included maple syrup [ 111 ], fruits such as strawberry (Fragaria × ananassa ) [ 112 ], pomegranate ( Punica granatum L.) [ 113 , 114 ], guarana ( Paullinia cupana Kunth) [ 115 ] and cranberry ( Vaccinium ) [ 116 ], and spices such as holy basil ( Ocimum sanctum ) [ 117 ] and turmeric ( Curcuma longa L.) [ 114 ]. Other tested natural products were the extracts of flowers such as red rose ( Rosa x hybrida ) [ 118 ], roselle ( Hibiscus sabdariffa L.) [ 119 ], horned violet ( Viola cornuta ), and pansy ( Viola x wittrockiana ) [ 120 ]; essential oils from Kushui rose ( Rosa setate × Rosa rugosa ) [ 121 ]; Japanese zelkova ( Zelkova serrata (Thunb.)…”
Section: Effects Of Natural Products In Caenorhabditis Eleg...mentioning
confidence: 99%